2013
DOI: 10.1186/1742-9994-10-35
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the origin of Cladocera by identifying heterochrony in the developmental sequences of Branchiopoda

Abstract: IntroductionOne of the most interesting riddles within crustaceans is the origin of Cladocera (water fleas). Cladocerans are morphologically diverse and in terms of size and body segmentation differ considerably from other branchiopod taxa (Anostraca, Notostraca, Laevicaudata, Spinicaudata and Cyclestherida). In 1876, the famous zoologist Carl Claus proposed with regard to their origin that cladocerans might have evolved from a precociously maturing larva of a clam shrimp-like ancestor which was able to reprod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 75 publications
1
43
0
Order By: Relevance
“…This fusion in the optic system varies throughout several taxa of the Branchiopoda. A single Bcyclopean^eye is present in all cladocerans (e.g., Fritsch et al 2013;Kirsch and Richter 2007) and in members of their cyclestheridan sister group, thus showing their close relationship (Fritsch et al 2013;Fritsch and Richter 2012;Olesen et al 1996). Despite the fused eyes, the degree of fusion of the optic ganglia varies among the cladocerans (Hanström 1928;Kirsch and Richter 2007;Leder 1915), and these arise from separate anlagen early in development (Threlkeld 1979;Ungerer et al 2011).…”
Section: The Lamina and The Visual Tectum Of Daphniamentioning
confidence: 96%
See 1 more Smart Citation
“…This fusion in the optic system varies throughout several taxa of the Branchiopoda. A single Bcyclopean^eye is present in all cladocerans (e.g., Fritsch et al 2013;Kirsch and Richter 2007) and in members of their cyclestheridan sister group, thus showing their close relationship (Fritsch et al 2013;Fritsch and Richter 2012;Olesen et al 1996). Despite the fused eyes, the degree of fusion of the optic ganglia varies among the cladocerans (Hanström 1928;Kirsch and Richter 2007;Leder 1915), and these arise from separate anlagen early in development (Threlkeld 1979;Ungerer et al 2011).…”
Section: The Lamina and The Visual Tectum Of Daphniamentioning
confidence: 96%
“…Despite the fused eyes, the degree of fusion of the optic ganglia varies among the cladocerans (Hanström 1928;Kirsch and Richter 2007;Leder 1915), and these arise from separate anlagen early in development (Threlkeld 1979;Ungerer et al 2011). In other branchiopods, the compound eyes are positioned very close to each other, as, e.g., in Triops and Lepidurus (Notostraca) (Fritsch et al 2013;Fritsch and Richter 2010;Harzsch and Walossek 2001).…”
Section: The Lamina and The Visual Tectum Of Daphniamentioning
confidence: 96%
“…Patterns of heterochrony may contain useful phylogenetic signal, as demonstrated by, e.g., Guralnick and Lindberg ( 2001 ), who produced a phylogenetic tree of several lophotrochozoan taxa based on the timing of cell lineage events and found that the phylogenetic hypothesis thus obtained replicated patterns found in more traditional analyses. In another study, patterns of heterochrony in the developmental sequences of Branchiopoda were used to identify the origin of Cladocera (Fritsch et al 2013 ).…”
Section: Tempo and Mode In Evolution Heterochrony In Phylogenetics: Nmentioning
confidence: 99%
“…It was Carl Claus in 1876, who claimed that cladocerans [3] had evolved from free-swimming 'conchostracan' larvae (clam shrimps). Among the Branchiopoda, Cladocera encompasses the morphologically most diverse group [3].…”
Section: Introductionmentioning
confidence: 99%
“…It was Carl Claus in 1876, who claimed that cladocerans [3] had evolved from free-swimming 'conchostracan' larvae (clam shrimps). Among the Branchiopoda, Cladocera encompasses the morphologically most diverse group [3]. Cladocera are commonly known as 'water fleas' due to their jerky swimming movements facilitated by their paired second antennae [4].…”
Section: Introductionmentioning
confidence: 99%